Pay attention, please! – A study of students attention in science experimental activities using electroencephalograms - Michelle Camara Pizzato; Patrik de Souza Rocha; Marcelo Diedrich de Souza; Clarice Monteiro Escott (Amazônia)
This article aims to present an investigation of students attention during the performance of an experimental science activity and to analyze the possible relationships between the students attention and the didactic actions involved during the performance of the activity. Therefore, portable electroencephalograms (EEG) were used as tools to determine the participants' attention during the activity. The research involved the analysis of EEG data in the form of graphs of attention intensities issued by the Effective Learner application and responses to questionnaires on prior and later conceptions and self-reported attention of four volunteer students over 18 years old in the first year of high school in a public school participating in the project. The results showed very different total times of greater and lesser attention for the 4 participants, but common didactic actions associated with greater student attention.